Central Bank Digital Currency: Constitutional Reconfiguration of Monetary Sovereignty Within Web3 Architectures - Siska Sanjahaya Jahir; Nunut Asniar (Yayasan Cahaya Generasi Positif, 2026)
The emergence of decentralized Web3 architectures fundamentally disrupts traditional territorial monetary sovereignty, thereby challenging the constitutional mandate of state-controlled currency. This study examines the normative collision between algorithmic decentralization and state-centric monetary frameworks under the Indonesian Constitution. Employing a doctrinal legal methodology through statutory, conceptual, and functional comparative approaches, this research analyzes the central bank digital currency as a critical constitutional defense mechanism. The findings indicate that the Financial Sector Omnibus Law positions the digital fiat as a sovereign instrument to restore macroeconomic control against transnational private stablecoins. Furthermore, balancing anti-money laundering obligations with constitutional privacy rights explicitly requires a regulation-by-design architecture, specifically implementing tiered anonymity. The institutionalization of digital fiat necessitates precise legal agency attribution within permissioned smart contracts to prevent algorithmic immunity. Ultimately, this regulatory integration represents a manifestation of digital constitutionalism, renegotiating the cyberspace social contract to ensure monetary stability while proportionally protecting all fundamental civic rights.